Analisis Kekasaran Permukaan Pada Pengaruh Kecepatan Spindel Dan Feeding Terhadap Material Baja AISI 1045 Pada Mesin Bubut CNC - Aththabary Priatama, Muhammad Rizllah; Oktriadi, Yudi; Zulfitriyanto, Zulfitriyanto (Jurnal Inovasi Teknologi Terapan, 2023)
In this era of increasingly advanced industrial technology development, of course, everyone wants the best results in making a product. For example in the machining process, one of which is CNC lathe machining, the level of roughness of a product really needs to be reviewed. The minimum surface roughness shows that the quality of a CNC machining process is very good, because the smaller the surface roughness value, the greater the quality value of a product, therefore in order to achieve this goal it is necessary to set the right parameters. Parameters varied were spindle speed (Rpm) and feeding. In this study the method used is the experimental method, with a combination of parameters to obtain surface roughness values. The material used is AISI 1045 steel, with the results of the data being analyzed using the Taguchi Smaller the Better method in Minitab 21.3 software. From the results of the calculation of the mean factor, the percent contribution to the spindle speed was obtained at 56.28%, while at feeding it was obtained at 38.14%. The optimal roughness value is obtained from the combination of parameters in the CNC lathe process on AISI 1045 steel which can make the optimal response value obtained at a spindle speed of 1645 rpm and a feeding of 0.18 mm/rev.